2022
DOI: 10.3390/separations9030061
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-High-Performance Micellar Liquid Chromatography Comparing Tween 20 and Tween 40 for the Determination of Hydroxycinnamic Acids

Abstract: A simple and green ultra-high-performance micellar liquid chromatography (MLC) method was developed here, comparing Tween 20 and Tween 40 for the first time as the only mobile phase modifiers with a C18 column. Its application to the separation of nine hydroxycinnamic acid (HCA) derivatives (cinnamic, caffeic, ferulic, sinapic, o-, m-, p-coumaric, 3,4-dihydroxyhydrocinnamic, and chlorogenic acids) was made, due to their importance as antioxidants in a variety of natural beverages such as wine and coffee. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Stationary phase temperature, surfactant concentration and type, and co-eluents are the three most crucial chromatographic factors. To increase separation effectiveness and shorten the retention period, the working column temperature should be higher than the Kraft point [38][39][40].…”
Section: Surfactants As a Mobile Phasementioning
confidence: 99%
“…Stationary phase temperature, surfactant concentration and type, and co-eluents are the three most crucial chromatographic factors. To increase separation effectiveness and shorten the retention period, the working column temperature should be higher than the Kraft point [38][39][40].…”
Section: Surfactants As a Mobile Phasementioning
confidence: 99%
“…The increased temperature contributes to faster mass transfer kinetics, which often improves the separation efficiency [67]. Generally, the increase in the column temperature leads to a shorter retention time of the analytes [68,69]. However, in some cases, it was observed that higher column temperature contributed to the increased value of the tailing factor [69].…”
Section: Surfactants As a Mobile Phasementioning
confidence: 99%
“…The application of the DoE approach during the mixed MLC method development facilitates the optimization of the critical chromatographic parameters such as concentration of SDS and Brij-35 and allows timely perception of their interaction. Polysorbates are another type of nonionic surfactant that can be used for MLC, including polysorbate 20 (Tween 20) or polysorbate 40 (Tween 40) [68,73]. The comparison of the influence of Tween 20 and Tween 40 as eluents in the MLC mobile phase on the retention of hydroxycinnamic acid compounds showed that shorter retention times and better peak shapes are observed using Tween 20 [68].…”
Section: Surfactants As a Mobile Phasementioning
confidence: 99%
See 1 more Smart Citation